PENGARUH MEDIA APLIKASI WORDWALL BERBASIS WEB PADA PEMBELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Yani, Zalma Putri; Sitohang, Risma (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to determine the influence of the web-based wordwall application media on learning science and science material, My Indonesia is Rich in Culture to improve the learning outcomes of class IV students at SD N 104204 Sambirejo Timur T.A 2023/2024. The population in this study was class IV students at SD N 104204 East Sambirejo, consisting of 2 classes, namely class IV-A and IV-B, each of which class IV-A had 22 students and class IV-B had 22 students. The research sample used the Total Sampling technique, namely using the entire existing population. This type of research is a quasi experimental design using a Pretest-Posttest Nonequivalent Control Group Design. Before conducting research, the research instrument was tested, namely testing the validity, reliability, distinguishability and difficulty of the instrument. The next stage the two sample classes will be given a pretest (initial test), then the experimental class will be given treatment using the wordwall application media and the control class will use the conventional method (lecture) and the next stage will be given a posttest (final test). Based on the results of the normality test, the significance result was 0.130, followed by the homogeneity test, the significance result was 0.832 and the results of the hypothesis test stated that there was an influence with a significance value of 0.001. So it can be concluded at the final stage through hypothesis testing that Ha is accepted and H0 is rejected.